Exploring Financial Management Behavior among University Students: A Grounded Theory Approach - Cahyono, Dwi; Aspirandi, Mirwan; Gusmao, Cristino; Bakti, Surya; Junaidi, Junaidi; Lestari, Evi (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This research explores the interaction between financial literacy, attitudes, self-control, and social factors in shaping the financial behavior of students in Indonesia, incorporating the roles of fintech and social media. A qualitative grounded theory approach was employed, using in-depth interviews with 20 purposively selected participants. Findings reveal that although students have access to various financial information sources, their literacy and application levels remain limited. Their financial behavior is heavily influenced by social pressure, the fear of missing out phenomenon, and social media, often leading to impulsive spending. Families play a crucial role in forming early financial habits, while self-control is key to managing spending temptations. Students developed adaptive strategies like saving, reducing expenses, and using financial apps to overcome challenges. The study concludes that a holistic approach, enhancing financial literacy, strengthening self-control, and educating on the social-digital environment, is essential to improve student financial behavior. These implications provide a basis for developing more effective and contextual financial education programs in higher education.